Die Lukaanse Jesusbeeld: In dialoog met Wilhelm Bousset se "Kyrios Christos" - Zyl, Sanrie van (Hervormde teologiese studies, 1997)
The Lucan image of Jesus: In dialogue with Wilhelm Bousset's 'Kyrios Christos'. Wilhelm Bpusset poses in his epoch-making work tKyrios Christos: Geschichte des Christusglaubens von den Anftingen des Christentums bis Irenaeus' the question of the context and reference of the title 'Kyrios Christos'. He concludes that this title reflects the Luke-Acts image of Jesus, originating from a pagan Hellenistic background. This paper follows the argument of Bousset concerning the titles 'Christos' and tKyrios' and examines co"ectiorzs given on his views. From this evaluation the conclusion is drawn that the Christology of Luke-Acts should be viewed as originating in the Antiochian Christian community, and thus against a Israelite-Hellenistic background. Jesus is represented as the risen Lord, the Messiah ruling his church. However, this conclusion doesn't account for Luke-Acts as a narrative, nor does it reflect an intensive study of the social and cultural world of the text. Therefore the possibilities of using a social-scientific as well as an "atological approach in dealing with the title 'Kyrios Christ os ' will be explored.